Lifting the lockdown: What are the options for low and middle-income countries? - Chowdhury, Rajiv; Luhar, Shammi; Khan, Nusrat; Choudhury, Sohel Reza; Matin, Imran; Franco, Oscar H. (Social Science Research Network (SSRN), 2022)
This article was published in The Social Science Research Network(SSRN) and the definite version is available at: http://dx.doi.org/10.2139/ssrn.3625605 The Article's website is at: https://papers.ssrn.com/sol3/papers.cfm?abstract_id=3625605